Multi—Peakon Solutions for Two New Coupled Camassa—Holm Equations*Supported by the National Natural Science Foundation of China under Grant No. 11261037, the Natural Science Foundation of Inner Mongolia Autonomous Region under Grant No. 2014MS0111, the Caoyuan Yingcai Program of Inner Mongolia Autonomous Region under Grant No. CYYC2011050, the Program for Young Talents of Science and Technology in Universities of Inner Mongolia Autonomous Region under Grant No. NJYT14A04. (1st June 2016) - Li 李, Yuan-Li 园丽; Zha 扎, Qi-Lao 其劳
Abstract: We study the multi—peakon solutions for two new coupled Camassa—Holm equations, which include two-component and three-component Camassa—Holm equations. These multi—peakon solutions are shown in weak sense. In particular, the double peakon solutions of both equations are investigated in detail. At the same time, the dynamic behaviors of three types double peakon solutions are analyzed by some figures.